Prevalence of and coping mechanisms against mental and psychological burnout among healthcare professionals in a Malaysian public hospital: A cross-sectional study - Nuratikah Adillah Rezuan; Aina Amanina Abdul Jalil; Zakiah Mohd Noordin (Malaysian Family Physician)
Introduction: Burnout is a significant issue among healthcare professionals, primarily including doctors, nurses and pharmacists. This study aimed to identify the factors contributing to burnout and the coping mechanisms employed by healthcare professionals working in a public hospital in Malaysia. Methods: This study used an analytic observational method with a cross-sectional design, collecting data via online and printed questionnaires. Healthcare professionals from Hospital Raja Permaisuri Bainun were recruited through non-probability convenience and snowball sampling. Descriptive statistics were utilised to analyse the prevalence of and coping mechanisms against mental and psychological burnout, while Pearson’s chi-square and inferential statistics were used to identify the association between burnout and socio-demographic factors such as age, sex and educational level, with P-values of <0.05 indicating statistical significance. Results: Approximately 54.7% of the participants had moderate burnout. The majority experienced personal and work-related burnout (81.9%) and patient-related burnout (85.5%). Significant associations were found between burnout and age (P<0.001). Religion was the most commonly utilised coping mechanism by the participants. Conclusion: The results underscore the urgent need for government institutions to implement targeted interventions and training programmes aimed at addressing burnout among healthcare professionals. Focusing on these issues can enhance mental health support, improve job satisfaction and ultimately ensure better patient care outcomes.